Capabilities and Reputation Risks Towards Firm Performance - Noraznira Abd Razak; Najihah Hanisah Marmaya; Mohd Zailani Othman; Idris Osman; Suhailah Kassim; Fatin Aqilah Maskuri; Nik Kutina Mat Tahir (MDPI, 2023)
The effects of firm-specific resources on firm performance has been a quest of many and widely studied worldwide. In today’s business environment, arguments suggesting the relative importance of firm-specific resources in explaining firm performance variation are said to be of the greatest influence on the study of firm behavior. On the other hand, firms with strong, positive reputations can attract and retain crucial talent and often have loyal customers likely to buy a broader range of products and services. It can lead to higher sales generated by satisfied customers and their referrals and can potentially raise capital and share price, and improve the firm performance. An empirical study such as this attempts to investigate the combinations of resources of the firm and focus on reputational risk management concerning firm performance. As such, this study involves variables partially adopted from Donabedian Theory, such as intangible resources, namely capability as an exogenous construct towards endogenous construct and firm performance, as well as proposing a mediation model to analyze the mediated relationship of reputational risk in accelerating the relationship between capabilities and firm performance. This study applies variance-based structural equation modeling via Smart PLS to a sample of 161 listed firms in Malaysia as respondents. A judgment purposive sampling technique has been adopted as the respondents are derived from listed firms under Malaysian Bourse. Overall, the findings of this study reveal how firms may gain competitive advantages in terms of their reputation and eventually be able to sustain their firm’s performances by implementing an integrative model of intangible resources such as capabilities and in their routines and processes within the firms.